EKONOMI HIJAU PERSPEKTIF EKONOMI POLITIK: RELEVANSI DAN IMPLEMENTASI DI INDONESIA - Ajeng Kartika Galuh; Asfi Manzilati; Sri Muljaningsih (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to investigate the relevance and implementation of the concepts of green economy and political economy in Indonesia through analysis of literature studies. The concept of a green economy emphasizing sustainable and environmentally friendly economic growth is becoming increasingly relevant amid the challenges of climate change and environmental degradation faced by Indonesia. Meanwhile, political economy is a key theoretical basis in understanding how economic decisions related to green practices are influenced by political, economic and policy factors at the local, national and global levels. Research findings show that there is a gap between concept and implementation in the field. Despite the commitment and efforts made by the government, private sector and civil society to encourage a green economy, there are still challenges in facing conventional economic interests which tend to focus on economic growth without taking environmental impacts into account. The implications of this research are the need for cross-sector collaboration, stronger regulations, investment in green innovation, and increased public awareness as important steps in realizing sustainable and environmentally friendly economic development in Indonesia.